Combination between acidity amendments and sewage sludge with phosphorus on soil chemical characteristics and on development of castor bean - Capuani, Silvia [UNESP]; Fernandes, Dirceu Maximino [UNESP]; Rigon, João Paulo Gonsiorkiewicz [UNESP]; Ribeiro, Lívia Cristina [UNESP] (Taylor & Francis, 2015)
The addition of urban and industrial waste products to agriculture not only provides them with an adequate environmental destination but also increases the nutrient content and negative charges in the soil, especially in naturally acidic tropical soils with high phosphorus-fixing capacity, just as liming does in relation to the dependent charges of pH. Both cases make it possible to favor the availability of phosphate fertilization. The aim of this study was to assess the interactions between application of composted sewage sludge (SSS) and soluble phosphorus (P) in combination with different rates of limestone (LS) and steel slag (SS) on the characteristics of dwarf castor bean and soil chemical properties. The experiment was conducted in a greenhouse in Botucatu, SP, Brazil. The Oxisol soil used was incubated with the combinations— based on chemical analyses of the soil, the waste product and slag, considering the needs of castor bean—in the 45 days prior to sowing, undertaking analysis of castor bean growth and dry-matter weight after physiological maturity, the time at which soil analysis was performed. SSS as an amendment of soil acidity provided better results in the properties of soil acidity, sum of bases (SB), cation exchange capacity (CEC), and base saturation (BS%). The combinations of the amendments were similar in regard to the increase of P availability in the soil. Although SSS alone resulted in an increase in organic matter (OM), nitrogen (N), magnesium (Mg), potassium (K), boron (B), cupper (Cu), zinc (Zn), and iron (Fe) contents in the soil, the low P content in the waste product extended the castor bean cycle, requiring P supplementation in combination.
Keywords: Organic waste; Phosphate fertilization; Ricinus communis L.; Silicate